Mulher, casamento e autoria feminina: enfoques na literatura infantil e juvenil de Marina Colasanti - Farias, Morgana de medeiros (2017)
The present research aims to analyze the literary production by the Brazilian writer Marina Colasanti, having selected four short stories published in the book Doze reis e a moça no labirinto do vento (2006), by the same author. We observed along our study that women`s literary production has been put aside along centuries in terms of canon formation, a review still necessary to be made. The male author has been taken as the pattern of the writing process, what reinforced cultural patriarchal values. This has been changing recently but is still so in many ways. Thus, our proposal connects us to several other emancipatory movements of society and, in terms of literature, to those which work in order to recognizes writing by women, being supported by gender studies as well as by literary criticism in general. In fact, gender is our central category of analysis along the study, in order to verify how marriage is represented in the short stories selected. We are interested in focusing the role women take inside the marriage institution, problematizing its fixity. Besides this gender approach in general terms, we decided to analyze these narratives as ways of making young students read and analyze in more empowering ways the gender roles offered to them (in books and in society). Our methodology is organized through the reading of the bibliographical material on gender and literary criticism, while constructing a questioning discourse on assumed gender roles at schools, believing the short stories can be read in more productive ways. Such a reading might help break with excluding gender concepts, while questioning the naturalized role frequently attached to women in common short stories for the young public.